Allosteric Regulation of CRISPR-Cas9 for DNA Targeting and Cleavage - Zuo, Zhicheng (Curr Opin Struct Biol, 2020)
The CRISPR-Cas9 system from Streptococcus pyogenes has been exploited as a programmable RNA-guided DNA targeting and editing platform. This evolutionary tool enables diverse genetic manipulations with unprecedented precision and ease. Cas9 is an allosteric enzyme, which is allosterically regulated in conformational activation, target recognition, and DNA cleavage. Here, we outline the underlying allosteric control over the Cas9 complex assembly and targeting specificity. We further review the strategies for mitigating intrinsic Cas9 off-target effects through allosteric modulations and the advances in engineering controllable Cas9 systems that are responsive to external allosteric signals. Future development of highly specific, tunable CRISPR-Cas9 systems through allosteric modulations would greatly benefit applications that require both conditional control and high precision.